The new local interstellar spectra and their influence on the production rates of the cosmogenic radionuclides 10Be and 14C. Issue 1 (3rd January 2017) - Herbst, K.; Muscheler, R.; Heber, B.
Abstract: With Voyager1 crossing the outer boundary of our solar system at the end of 2012, for the first time in the instrumental era an unmodulated local interstellar spectrum (LIS) at galactic particle energies below 500 MeV has been measured. On the basis of these as well as Payload for Antimatter Matter Exploration and Light‐nuclei Astrophysics (PAMELA) and Alpha Magnetic Spectrometer (AMS02) measurements, most recently, three new LIS models have been proposed in the literature. In this study we compare the newest LIS models to previously most often used ones. Thereby, we investigate and discuss the influence of these LIS models on the terrestrial production rates of the cosmogenic radionuclides 10 Be and 14 C, which are produced due to the interaction of galactic and solar cosmic rays with atmospheric constituents. After being transported within the atmosphere they are preserved in natural archives such as, e.g., ice sheets or tree rings, forming a unique tool to study the solar modulation of thousands of years back in time. To parameterize the heliospheric modulation we apply the force‐field approximation for the individual LIS models from which LIS‐dependent solar modulation parameter (ϕ) values are derived. Furthermore, we present updated sets of linear regression functions containing the opportunity to convert the LIS‐dependent ϕ values between the investigated LIS models. The results are then applied to a long‐term reconstruction of the solar modulation parameter. Key Points: Comparison of the new LIS models with previously used models Investigation of the LIS‐dependent differences in the 10 Be and 14 C production rates Updated reconstruction of the solar activity over the past 1000 years